1986
DOI: 10.1093/oxfordjournals.eurheartj.a062035
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal ST segment changes in acute inferior myocardial infarction: clinical, haemodynamic and angiographic implications

Abstract: Reciprocal ST segment changes are frequent during acute inferior myocardial infarction, yet their significance remains controversial. In order to investigate the implications of these changes, the ECG obtained on admission for 83 patients with acute inferior myocardial infarction was compared with the clinical course and the results of angiographic and coronary arteriographic studies performed an average of 3 weeks after the onset of symptoms. Group 1 consisted of 59 patients with at least 1 mm of horizontal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…2 , right). These findings also mimicked the reciprocal ST segment changes frequently observed in human inferior wall myocardial infarction [ 5 , 21 ]. In general, the presence of reciprocal changes in ECG reflects the extent of myocardial ischemia [ 8 ] and supports the diagnosis of acute myocardial infarction [ 3 , 24 ].…”
supporting
confidence: 77%
“…2 , right). These findings also mimicked the reciprocal ST segment changes frequently observed in human inferior wall myocardial infarction [ 5 , 21 ]. In general, the presence of reciprocal changes in ECG reflects the extent of myocardial ischemia [ 8 ] and supports the diagnosis of acute myocardial infarction [ 3 , 24 ].…”
supporting
confidence: 77%
“…As PET imaging is limited by the requirement to perform the study hyperacutely, at the actual time of reciprocal change, these findings were limited to just nine patients, all of whom had inferior territory infarction. Gibelin et al 20 also studied inferior infarction using biplane X-ray ventriculography and concluded that reciprocal changes were associated with adverse left ventricular function and increased in-hospital complication rate in 83 patients. An evaluation of 44 patients using radionuclide ventriculography found similar associations 2.…”
Section: Discussionmentioning
confidence: 99%
“…The ECG of our case showed, during PCI, no reciprocal ST segment depression in anterior derivations and ST elevation only in V1-V4 leads. In the occurrence of anterior ST segment depression during acute inferior MI, the proposed explanations vary from extensive inferoposterior infarction or additional anterior ischemia to a reciprocal change [5][6][7].…”
Section: Right Ventricular Myocardial Infarction (Mi) Is Normallymentioning
confidence: 99%